Chiral drugs (Ashgate, 2001)
Chiral Drugs provides an introduction to the types of sources and methods currently in use for obtaining chiral molecules and is an invaluable resource for researchers in the pharmaceutical and biotechnology sectors as well as to those working in the basic biochemical sciences. Chiral Intermediates provides an introduction to the types of sources and methods currently in use for obtaining chiral molecules and is an invaluable resource for information on available chiral molecules. Chiral Intermediates and Chiral Drugs are the most comprehensive and detailed guides to chiral compounds available.